Phycocyanin from Spirulina platensis Induces Cytotoxicity and Apoptosis in T47D Cells - Safira Chairani Dimarti; Neni Susilaningsih; Renni Yuniati (Biosaintifika: Journal of Biology & Biology Education, 2020)
Breast cancer cases in Indonesia have risen in alarming rate. Herbal medicines have been developed to complement conventional cancer therapy and to lessen the negative effects of the therapies. Phycocyanin, blue-green photosynthetic pigment from Spirulina platensis, becomes a potential candidate of herbal medicine for cancer therapy due to its capability to eliminate various cancer cell line on in vitro level. This research aimed to analyse the effectivity of phycocyanin to induce cytotoxic and apoptotic activity of T47D cells (breast cancer cell line). MTT assay was perform to measure IC50 value. Double-staining assay and flow cytometry were applied to visualize the appearance of apoptotic cells and to measure the percentage of apoptotic and necrotic cells. Result showed that the IC50 value of phycocyanin towards T47D cells is 1650 Î¼g/mL. Phycocyanin was also proven to induce apoptosis at IC50 with the apoptosis percentage of 45.93%. This research presented different results from previous researches that used phycocyanin from saltwater Spirulina platensis. Based on the results of this study, phycocyanin has the potential to be developed as anticancer agent by inducing apoptosis.